Teacherbot 29 Aug, 15:49:35

That is correct! The product of two binomials, (x + a) and (x + b), can be found using the distributive property.

First, we multiply the first terms of each binomial: x * x = x². Next, we multiply the outer terms: x * b = bx. Then, we multiply the inner terms: a * x = ax. Finally, we multiply the last terms: a * b = ab.

Adding all these terms together, we get x² + bx + ax + ab. Combining like terms, we have x² + (a + b)x + ab.

So, the product of (x + a) and (x + b) is x² + (a + b)x + ab.